2021
DOI: 10.1242/jcs.258186
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-dependent protein acyltransferase DHHC21 controls activation of CD4+ T cells

Abstract: Despite the recognized significance of reversible protein lipidation (S-acylation) for T cell receptor signal transduction, the enzymatic control of this post-translational modification in T cells remains poorly understood. Here, we demonstrate that DHHC21, a member of the DHHC family of mammalian protein acyltransferases, mediates T cell receptor-induced S-acylation of proximal T cell signaling proteins. Using Zdhhc21dep mice expressing a functionally deficient version of DHHC21, we show that DHHC21 is a calc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Future work will evaluate if Orai1 can also be S-acylated by DHHC21 and determine the DHHC enzyme(s) responsible for STIM1 S-acylation. Of note, we have shown dramatic defects in T cell function in DHHC21 mutant mice in vitro and in vivo which may be consistent with alterations in SOCE (25).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Future work will evaluate if Orai1 can also be S-acylated by DHHC21 and determine the DHHC enzyme(s) responsible for STIM1 S-acylation. Of note, we have shown dramatic defects in T cell function in DHHC21 mutant mice in vitro and in vivo which may be consistent with alterations in SOCE (25).…”
Section: Discussionsupporting
confidence: 79%
“…It has been shown that DHHC20 S-acylates Orai1 (12). We have shown that many TCR pathway components are S-acylated by the PM-localized DHHC21 (25-28). Future work will evaluate if Orai1 can also be S-acylated by DHHC21 and determine the DHHC enzyme(s) responsible for STIM1 S-acylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that many TCR pathway components are S-acylated by the PM-localized DHHC21. We have shown that the DHHC21 binds to calcium/calmodulin ( 27 ). Mutation of the calcium/calmodulin site of DHHC21 in the depilated mouse leads to defects in T-cell activation and differentiation into its subsets establishing in vivo relevance ( 27 , 28 , 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the DHHC21 binds to calcium/calmodulin ( 27 ). Mutation of the calcium/calmodulin site of DHHC21 in the depilated mouse leads to defects in T-cell activation and differentiation into its subsets establishing in vivo relevance ( 27 , 28 , 29 , 30 ). Future work will evaluate if Orai1 can also be S-acylated by DHHC21 and determine the DHHC enzyme(s) responsible for STIM1 S-acylation.…”
Section: Discussionmentioning
confidence: 99%